Concomitant vs Staged Therapeutic Inguinal Lymphadenectomy in Clinically Node Positive Penile Squamous Cell Carcinoma: Does It Make a Difference?. Issue 3 (18th March 2023) - Huelster, Heather L.; Chang, Andrew; Rose, Kyle M.; Bandini, Marco; Albersen, Maarten; Roussel, Eduard; Chipollini, Juan; Zhu, Yao; Ye, Ding-Wei; Ornellas, Antonio A.; Catanzaro, Mario; Marandino, Laura; et al.
Abstract : Purpose: Inguinal lymph node dissection within 3 months of primary tumor resection in penile cancer has been associated with longer recurrence-free and cancer-specific survival. However, the optimal timing and effect of lymphadenectomy performed concurrently at the time of primary lesion management on oncologic outcomes in clinically lymph node positive penile squamous cell carcinoma remains unknown. Materials and Methods: An international, multicenter cohort of 966 penile cancer cases was queried for penile squamous cell carcinoma management after the year 2000, clinically lymph node positive status, and performance of penile surgery and inguinal lymph node dissection. Cohorts were stratified as concomitant if inguinal lymph node dissection and penile surgery occurred on the same date or staged when inguinal lymph node dissection was performed after penile resection. Rates and patterns of penile squamous cell carcinoma recurrence were reported. Distant recurrence-free, cancer-specific, and overall survival were estimated using Kaplan-Meier analyses and groups compared with log-rank testing. Results: Of 253 contemporary men with clinically lymph node positive penile squamous cell carcinoma, 96 (38%) underwent concomitant inguinal lymph node dissection and 157 (62%) had inguinal lymph node dissection performed in a staged manner. Penile cancer was most likely to recur distantly (19%) followed by in the groin (14%) or pelvis (5%). There were no differences in distant recurrence-free, cancer-specific, or overall survival between management strategies. Multivariable analysis adjusting for stage, treatment center, and perioperative chemoradiation also demonstrated no recurrence-free, cancer-specific, or overall survival benefit between management strategies. Conclusions: Inguinal lymph node dissection performed concurrently with excision of the penile tumor for clinically node positive penile squamous cell carcinoma is not associated with differences in recurrence-free, cancer-specific, or overall survival compared to staged lymph node dissection.